INTERAKSI SIMBOLIK PADA TRADISIROKAT SAWAH DI KABUPATEN SITUBONDO - Dendi Agung Prayuda; Aminul ‘Alimin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
Indonesia is known as a diverse country with many tribes, cultures and traditions. One of the many traditions that exist in Indonesia is the rokat rice field tradition in the Madurese community, more precisely in Sumberanyar Village, Jatibanteng District, Situbondo Regency, East Java. The Rokat Sawah tradition is an ancestral tradition that has been carried out since ancient times and continues until now. Symbolic interaction is a social relationship between people which is shown by the exchange o f symbols used by them, both individuals with individuals, individuals with groups and groups with other groups, the meaning of which they have mutually agreed upon. This research aims to describe the implementation procession and meaning of symbolic inter actions in the Rokat Sawah tradition in Sumberanyar Village, Jatibanteng District, Situbondo Regency, East Java. This research is qualitative research with data collection through interviews, observation and documentation with analysis through data collect ion and data presentation. The results of the research can be stated that, the procession of carrying out the rokat sawah tradition begins with inviting the farmers, the farmers gather in front of the lu'ulu house, together they go to the location of the r okat sawah tradition, prepare for the implementation of the rokat sawah tradition, the congregation sits in a circle around various foods , opening of the traditional Rokat Sawah event by Lu'ulu, reciting tawasul, yasin and tahlil, reading the Rokat prayer and ending with closing and eating together. In the interactions carried out by the people of Sumberanyar Village in the Rokat Sawah tradition there are symbols full of implied meaning, such as fostering a sense of togetherness and harmony, eliminating di scrimination between communities, realizing gratitude to Allah SWT, approaching oneself to the Creator, preserving ancestral traditions and rejection of balak.